Teacher training on the implementation of science research projects In classroom context - Esteves, Zita (2010)
The introduction of the use of science projects in the classroom in the context of teacher training is of great relevance, especially since the development of these projects in Portuguese schools is not a regular practice, despite the fact that their pedagogical importance had been widely proved. These advantages include the development of decision making skills and a critical mind, which are essential to the learning and understanding of science. In the school year of 2009/2010, a teacher training course on the development of science projects in the classroom was carried out. This course aimed at the creation of strategies for the implementation of the development of science projects, by the students, both in classroom context or as extracurricular activity. In this work, we present the strategies employed at this teachers training course. We also present the discussions and the different contributions received from the group of teachers involved in this activity, along with the proposed in-class/school implementation strategies and different examples.